2020
DOI: 10.1016/j.ijmedinf.2020.104164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Trust and Privacy Concerns on Technology Acceptance in Healthcare: An Indian Perspective

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
169
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(199 citation statements)
references
References 125 publications
(151 reference statements)
24
169
2
4
Order By: Relevance
“…If an individual perceives that the risk associated with the use of renewable energy is quite low as compared to other sources of energy, then that individual will likely adopt renewable energy and vice-versa [44]. Trust is considered as the willingness of an individual to be vulnerable to the actions taken by another individual or party, with the expectation that the trusted individual will perform particular actions in favor of the trusting individual [45]. From the perspective of renewable energy, trust in renewable energy implies the expectation of an individual the using the renewable energy resources will result in acceptable to favorable outcomes in terms of its benefits [46].…”
Section: Risk and Trust Perception Of Renewable Energymentioning
confidence: 99%
See 1 more Smart Citation
“…If an individual perceives that the risk associated with the use of renewable energy is quite low as compared to other sources of energy, then that individual will likely adopt renewable energy and vice-versa [44]. Trust is considered as the willingness of an individual to be vulnerable to the actions taken by another individual or party, with the expectation that the trusted individual will perform particular actions in favor of the trusting individual [45]. From the perspective of renewable energy, trust in renewable energy implies the expectation of an individual the using the renewable energy resources will result in acceptable to favorable outcomes in terms of its benefits [46].…”
Section: Risk and Trust Perception Of Renewable Energymentioning
confidence: 99%
“…The chi-square statistic for the model was significant (χ 2 [593] = 1315.745, p < 0.01). The χ 2 /df ratio = 2.128 was below 3.0 and was influenced by the sample size [45,47]. The CFI was 0.944; TLI was 0.938; IFI was 0.945, and NFI was 0.901, which provided an excellent fit since the values were greater than 0.9 or close to 1.0.…”
Section: Structural Equation Modellingmentioning
confidence: 99%
“…Perceived ease of use (PEU) is defined as the degree of comfort and effortlessness one experiences while using any kind of service. While the extent to which one finds the service is useful for him or her is termed as perceived usefulness (PU) [16]. Patients evaluate usefulness of telemedicine services based on the ease with they can use it.…”
Section: Theory Building and Hypotheses Developmentmentioning
confidence: 99%
“…Research by Elkaseh and Wong [17] revealed that PU and PEU are the significant determinants of acceptance of technology. Patients prefer to accept the telemedicine service only when they feel that by using this service, they will get better results.It has also been advocated by Dhagarra et al, [16] that if any technology will offer treatment to patients at the places of their convenience and at the same time will reduce their burden of carrying their case history physically will surely gravitate them to adopt the same, given that other major parameters remain the same. Based on the above facts the hypotheses 1, 2 and 3 are proposed.…”
Section: Theory Building and Hypotheses Developmentmentioning
confidence: 99%
“…Trust is another factor that could be effective for customers in the adoption of new technologies. A recent study shows that trust is a direct predictor of patients' behavior to accept technology in availing healthcare services (Dhaggara et al 2020). According to Alhogail (2018), trust in the context of IoT technologies is to rely on another asset that starts with the evaluation and expectations of consumers for the product or service to be used and to fulfill the expected or targeted purpose.…”
Section: Introductionmentioning
confidence: 99%